KAJI EKSPERIMENTAL MOTOR BAKAR BENSIN 2 LANGKAH DENGAN SISTEM PENYEMPROTAN LANGSUNG BAHAN BAKAR MEKANIS PADA RUANG BAKAR - Iman Kartolaksono Reksowardojo; Aan Setyawan; Budi Sudarwanto; Ibrahim Syaharuddin (Mesin, 2003)
In this study, a mechanical fuel direct injection system is used in a two-stroke 70 cc gasoline engine. The injection system is using a high pressure pump (injection pump) and an injector (Nozzle) from a 5 hp diesel engine that mechanically is operated by a cam. The modifications on the two stroke gasoline engine are unthrottle intake system, additional hole in the cylinder head for the injector and a camshaft system. The camshaft is connected to the crankshaft. Theperformance of the engine is tested and the result is compared with the performance of the carburetor system engine in the same testing condition. The performance of the direct injectionsystem engine is better than the carburetor system engine in 1600-1750 rpm range. The power of the engine increases in about 143%, the specific fuel consumption decreases in about 35%, the thermal efficiency increases in about 59%, the air intake increases in about 244%, the scavenging efficiency increases in about 110% and the air-fuel ratio increases in about 116%. The improvement of the performance is caused by the increase of the air-fuel ratio also causing a lean combustion and an unthrottle intake process. But in other operation condition the mechanical fuel direct injection system cannot operate with good performance because the system cannot full fill the need of a complex system control.